Profiling medulloblastoma and juvenile pilocytic astrocytoma brain tumours in a South African paediatric cohort - Nair, Omesan (Division of Neurosurgery, 2018)
Brain tumours in children are one of the most challenging diseases to treat, and so outcomes are variable and often lacking. There are currently no reliable data of presentation of disease, the spectrum of tumours treated, how these are treated, and what the outcomes are for children in South Africa, and certainly no molecular biology data. In this respect, this thesis investigated the two commonest types of childhood brain tumour, the highly malignant Medulloblastoma (MB) and the generally less aggressive Juvenile Pilocytic Astrocytoma (JPA) with relation to their molecular biology and their clinical correlates to begin to address this gap and build capacity for further molecular-based studies in an African context. The study design in this thesis takes a systematic approach and is structured into MB and JPA biochemical characterisation followed by 4 studies of their respective proteomic profiles. The study design involved creating appropriate patient cohorts and determining sample characteristics for interpretation of results. The statistical power achieved in this thesis showed a minimum of 2-fold difference for a power greater than 0.8 in each case. Proteomic clustering was used to validate or delineate any discrepancies in subtype assignments for MB. Molecular profiles together with proteomic data of MB and JPA cases in this thesis provide evidence for some novel molecular pathways, proteins and peptides associated with pathogenesis. This work therefore provides extensive data that is hypothesis generating for further studies that could build upon molecular understanding in a South African and larger African context.